2009
DOI: 10.1021/jp901272k
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-Based Ionic Liquids. 1-Methyl Imidazolium Nitrate: Thermochemical Measurements and Ab Initio Calculations

Abstract: In this work data of the molar enthalpies of formation of the ionic liquid 1-methylimidazolium nitrate [H-MIM][NO3] was measured by means of combustion calorimetry. The molar enthalpy of fusion of [H-MIM][NO3] was measured using DSC. Experiments to vaporize the ionic liquid into vacuum or nitrogen stream in order to obtain vaporization enthalpy have been performed. Ab initio calculations of the enthalpy of formation in the gaseous phase have been performed for the ionic species using the G3MP2 theory. The comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Many reviews had shown the importance of IL such as in supercritical fluid applications by Seda Keskin et al [54]. Measurements of thermochemical properties of imidazolium-based ionic liquid (ILs) carried out has been reported [55]. Tamar L. Greaves et al [56] explained the properties and applications of protic ILs.…”
Section: Properties Of Imidazolium-based Ionic Liquidsmentioning
confidence: 99%
“…Many reviews had shown the importance of IL such as in supercritical fluid applications by Seda Keskin et al [54]. Measurements of thermochemical properties of imidazolium-based ionic liquid (ILs) carried out has been reported [55]. Tamar L. Greaves et al [56] explained the properties and applications of protic ILs.…”
Section: Properties Of Imidazolium-based Ionic Liquidsmentioning
confidence: 99%
“…drastically. [13][14] For instance, density of IL decreases as the length of the alkyl chain on the cation increases up to a certain length. For a given cation, the density increases as the molecular weight of the anion increases.…”
Section: Introductionmentioning
confidence: 99%
“…Calorimetric determination of the enthalpies of vaporization was reported in one work [3]. However, noncalorimetric techniques for determination of D g l H were used more often (for example, [4][5][6][7]). A review of the thermodynamics of IL vaporization has been recently published [8].…”
Section: Introductionmentioning
confidence: 99%
“…The enthalpies of formation have been obtained from the experimental data only for five ILs (table 1). The measurements were made either in combustion calorimeters [7,[26][27][28] or in a reaction calorimeter [10]. …”
Section: Introductionmentioning
confidence: 99%